Continuous high-altitude measurements of cosmic ray neutrons and SEU/MCU at various locations: correlation and analyses based-on MUSCA SEP³ - Hubert, G. (2013)
In this paper are described measurements at high-altitude of both radiation environment and effects. These measurements comprise cosmic ray neutrons and SBU/MCU on nanoscales devices. Results obtained at Pic-du-Midi, France, and in the city of Puno, Peru, are presented and analyzed. Analyses and cross comparisons based-on MUSCA SEP³ calculations show a good agreement between experimental data and modeling, thus illustrating the importance of the knowledge of the radiation field for a reliable prediction.